Exploring barriers and educational needs in implementing dual-task training for Parkinson’s disease: insights from professionals - Domingos, Josefa; Dean, John; Fernandes, Júlio Belo; Família, Carlos; Fernandes, Sónia; Godinho, Catarina (Frontiers in Medicine, 2024)
There is growing evidence suggesting that dual-task training benefits people with Parkinson's disease (PD) on both physical and cognitive outcomes. However, there is no known data regarding professionals' educational needs and barriers to its implementation. This study aimed to explore the barriers and educational needs of healthcare and exercise professionals to integrate dual-task training into their practice with people with PD.We conducted a study based on a web survey. Social media channels were used to recruit a convenience sample of exercise and healthcare professionals working with people with PD.Of the 185 eligible responses, the majority were physiotherapists (68,1%) followed by occupational therapists (10.8%). Most participants attended Parkinson-specific training (88,6%) and employed the treatments set up in individual one-on-one sessions (58,9%).We identified several barriers to dual-task training implementation, with lack of time (to prepare materials), staying creative and/or accessing new ideas, unreliable tools for measuring gains, and insufficient expertise as the most referred by participants. The educational needs most referred included accessing examples of interventions in general, knowing what strategies to apply and their application for people with different symptoms. Our results highlight that professionals remain challenged to integrate dual-task training into PD clinical care mainly due to knowledge gaps, difficulties in accessing new ideas, and lack of time.